A Symptom-based Disease Diagnosis: A Pre-Classification ML Approach - Rohith, Suram; Kalaiselvi, K.; Jawanth Reddy, K.; Venkata Rami Reddy, V.J. (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
In emergency hospitals, the hospital conveyance framework is seen as an important component of the clinical, financial, and executive well-being areas. This study incorporates Artificial Intelligence (AI) techniques to assess and investigate cases of various ailments that occur in low-income families. The proposed system utilizes unstructured and newly presented hospital data by applying the Machine Learning Certificate Tree computation. Mining anticipates hospitalization this study proposes a data-driven, scalable alternative to conventional diagnostic techniques by addressing the issues like unbalanced data and guaranteeing model interpretability.